Self-Microemulsifying Drug Delivery System of Phillygenin: Formulation Development, Characterization and Pharmacokinetic Evaluation - Lingzhi Wang; Wenrui Yan; Yurun Tian; Huanhuan Xue; Jiankai Tang; Liwei Zhang (MDPI AG, 2020)
Phillygenin, as an active ingredient of Forsythia suspensa, possesses a wide range of biological and pharmacological activity. However, its development and application are restricted due to its poor bioavailability and low solubility. Our work aimed to develop a self-microemulsifying drug delivery system to improve the oral bioavailability of phillygenin. The composition of the self-microemulsifying drug delivery system was preliminary screened by the pseudo-ternary phase diagram. Subsequently, the central composite design method was employed to optimize the prescription of the self-microemulsifying drug delivery system loaded with phillygenin. The prepared self-microemulsifying drug delivery system of phillygenin was characterized in terms of morphology, droplet size distribution, polydispersity index and stability. Then, the in vitro dissolution and the oral bioavailability were analyzed. The optimized self-microemulsifying drug delivery system of phillygenin consisted of 27.8% Labrafil M1944CS, 33.6% Cremophor EL, 38.6% polyethylene glycol 400 (PEG-400) and 10.2 mg/g phillygenin loading. The prepared self-microemulsifying drug delivery system of phillygenin exhibited spherical and uniform droplets with small size (40.11 ± 0.74 nm) and satisfactory stability. The in vitro dissolution experiment indicated that the cumulative dissolution rate of the self-microemulsifying drug delivery system of phillygenin was significantly better than that of free phillygenin. Furthermore, after oral administration in rats, the bioavailability of phillygenin was significantly enhanced by the self-microemulsifying drug delivery system. The relative bioavailability of the self-microemulsifying drug delivery system of phillygenin was 588.7% compared to the phillygenin suspension. These findings suggest that the self-microemulsifying drug delivery system of phillygenin can be a promising oral drug delivery system to improve the absorption of phillygenin.